Reading the Judeans and the Judean War in Martial's Liber spectaculorum - Chapman, Honora Howell (2012)
Martial's Liber spectaculorum celebrates spectacles at the Flavian amphitheatre, which was most likely built with money gained from the Judean War. This article contextualizes epigrams from Martial's Liber spectaculorum with evidence from the histories of Josephus and other sources, finding possible references to the Judeans in specific epigrams with anthropomorphized animals. It also takes into consideration an epigram from the Florilegium Gallicum, which has been published at the end of the Liber since the sixteenth century. In the Liber spectaculorum, Martial engages in a strategy of virtually silencing the Judean people—‘de Solymis … perustis’, as the poet says in Ep. 7.55—whose pillaged property built the Colosseum. This may, in part, be a result of the blending of epigrams from the reigns of both Titus and Domitian into a revised Liber featuring a single ‘Caesar’ who represents both emperors. Since Domitian never fought in the Judean War, Martial avoids—or has removed during revision—overt comments about victory in the Judean War. It is up to the reader, therefore, to find the Judeans quietly and ignominiously metamorphosed into animals to be punished in his text's arena, and finally, as losers who pay the price for rebellion.
Keywords: Domitian; Titus; Flavian; spectacle; Colosseum; Martial; Josephus; Judean/Jewish War